World Economy Summer 2023: Growth remains subdued - Klaus-Jürgen Gern; Stefan Kooths; Jan Reents; Nils Sonnenberg; Ulrich Stolzenburg (Kiel Institute for the World Economy (IfW Kiel), 2023)
A number of factors that contributed to the weakening of the global economy in the past year have recently improved significantly. Energy prices have reversed, the prospects for a steady expansion in China have improved with the abandonment of the zero-Covid policy, and supply bottlenecks have ceased to impede economic activity to an unusual extent. All this has helped the global economy to stabilize. However, the sharp tightening of monetary policy has led to significantly higher financing costs and is weighing on growth. Fiscal policy is generally also restrictive. Against this backdrop, global growth is expected to be moderate this year and next. After growing by 3.3 percent in 2022, which is roughly in line with the medium-term trend rate, global output is expected to grow by only 2.8 percent and 3.0 percent in 2023 and 2024, respectively. Compared to our spring forecast, we have increased the rate for 2023 by 0.3 percentage points but decreased it by 0.2 percentage points for 2024. Although inflation will fall significantly in the coming months on the back of lower commodity prices, underlying inflation is likely to remain elevated for the time being and will not return target levels before the end of the forecast horizon.
Keywords: 330; advanced economies; emerging economies; monetary policy; Fortgeschrittene Volkswirtschaften; Schwellenländer; Geldpolitik